Une catastrophe hors norme d'origine météorologique le 2 octobre 2020 dans les montagnes des Alpes-Maritimes - Pierre Carrega; Nicolas Michelot (Physio-Géo)
The exceptional rains of October 2, 2020, which affected the mountains of the Alpes-Maritimes, in southeastern France, will remain marked in the annals of statistics, and particularly in the minds of the inhabitants of the high valleys of the Vésubie and Roya, especially by their catastrophic consequences. The risk is described here by the articulation of three components that are the hazard, susceptibility and vulnerability.The hazard, the initial component consisting of rainfall and the mechanisms that generated it, is remarkable. Indeed, several factors combined to produce very strong air ascents over this region: a particularly powerful cyclone for the season, affecting unstable air in low layers, air very rich in water vapor after its overflight of the Mediterranean still warm in this season, and the rare coincidence of a very strong pressure gradient and its isobars oriented south-north with a steep and high relief, for more than 24 hours. To the west of the Var River (Grasse Pre-Alps), the south to south-southwest flow collided perpendicularly with the first reliefs near the sea oriented west-east (1200-1800 m in altitude), resulting in heavy rainfall totals exceeding 200, even 300 mm in 24 hours at 20-25 km from the coast, due to the orographic barrier effect. To the east of the Var River, the topography, this time oriented south-north, parallel to the low-level flow, led the latter far inland, with stormy winds forcing it to rise gradually but powerfully to the Mercantour ridge line (3000 m altitude). Cumulative rainfall measured reached 513 mm in 24 hours at Saint Martin-Vésubie and 663 mm (including 336 mm in 6 hours) at the Mesches lake (Roya watershed) 40 km from the coast, due to the guidance effect.Another originality is that the areas concerned are very extensive: it is estimated that about 2000 km2 received more than 200 mm, causing water levels of 50 to nearly 100 million cubic meters depending on the catchment area. The return periods of such rainfall are out of the ordinary, especially for Saint-Martin-Vésubie where the 7300 years are exceeded according to an adjustment with a GUMBEL law, or 486 to 5276 years (depending on parameter k) with a distribution of Generalized Extreme Values (GEV) which proves to be better adapted. At Tende (town), the return period reaches 550 years according to GEV (800 years according to a GUMBEL law). The station of Breil-sur-Roya is less affected with a value less than 100 years, the most abundant rains having fallen upstream. Huge volumes of water were able to infiltrate and run off, in proportions and at very variable speeds depending on the behavior of the raindrops on the surface of the ground, which is determined by the second component of the risk: susceptibility, the potential for the production of floods and ground movements following heavy rainfall.This generated phenomena of varying magnitude depending on the watersheds, depending on several parameters that distinguish, as their extent, pedology, lithology, or topography and slopes without forgetting the rate of vegetation cover. It is the combination of these parameters that made the flood generated more or less important and fast. At high altitudes, the steep slopes and the rather impermeable and bare ground allowed for the generation of vigorous runoff leading to an innumerable number of landslides and gullies on the sides of the valleys. These have fed the rivers and streams in fury with solid materials of all sizes, creating muddy devastating flows. If the floods have sometimes undermined entire sections of the riverbanks, they have also contributed to locally filling in the riverbed by raising it by several meters in some places.The combination of hazard and susceptibility has caused a major risk in terms of the vulnerability of the valley bottoms. Indeed, the stakes are high because they concentrate communication routes and populations often residing along the rivers, even in their major beds in some places. The alluvial or fluvioglacial soils, without cohesion, have been cleared by these floods with the houses and infrastructures that were there. The human and socio-economic toll is very high: nearly 20 deaths, traumatized populations, numerous buildings and houses totally destroyed or rendered uninhabitable, devastated and metamorphosed landscapes, dozens of bridges and kilometers of roads wiped out. By proposing an interpretation grid, the presentation of the intra- and inter-component articulation explains that this damage far exceeded that linked to the usual Mediterranean autumn floods (I. BARRET et al., 1994), as well as what could be imagined in reference to a secular collective memory. In spite of the human lives lost and the considerable material damage, the disaster could have been worse, if on the one hand the means of fight and immediate prevention had not been so well expressed, and on the other hand if there had not been a culture of risk, the degree of which is secularly rather high among the populations of these mountain valleys, compared to the city dwellers of the Côte d'Azur coast.[traduction effectuée sur https://www.deepl.com/fr/translator]